Integrating diversity of smallholder coffee cropping systems in environmental analysis - Acosta-Alba, Ivonne; Boissy, Joachim; Chia, Eduardo; Andrieu, Nadine (Springer, 2020)
Purpose Coffee represents an important trade asset internationally. Around 70% of global coffee production is provided by 25 million smallholders farmers. In recent decades, coffee systems have been transformed into more intensified systems of coffee monoculture. The general objectives of this paper are to provide a better picture of the traditional coffee cropping systems and postharvest processes on-farm and to assess the environmental impacts, integrating the diversity of smallholder cropping systems.